Early childhood educators' attitudes to science and science education. - Russo, Sharon (Curtin University, 1999)
It has long been acknowledged that pre-service Early Childhood teachers enter university with a notable lack of confidence, high levels of anxiety and an aversion to science and mathematics. Unless redressed during their time spent at university, such negative attitudes may ultimately influence the quality of science education these teachers offer to young children. This study considers the affective attitudes to science and science education of those people considered to be central to the education of young children.Specifically the study investigates the attitudes and backgrounds in science/ science education, of academics, pre-service and in-service teachers together with their attitudes towards teaching science to young children. The attitudes to science of a group of young children, aged between 4 and 8 years, were also investigated in the study. The potential links between the attitudes held by each group was of great interest to the researcher who considered the ways that academics promoted the teaching of science to young children, the factors influencing the willingness of pre-service and in-service teachers to present science to young children and the effect that teachers have on the responses of young children to science.The findings suggest that in contrast to the attitudes towards science of pre- and in-service teacher groups in the study, the young children and academics displayed attitudes such as interest, curiosity, confidence and enjoyment towards their experiences in science. There was a strong link between the memory of prior experiences in science and the present attitudes to science of the adult participants. The implications of the study are that science education in the early years will be enhanced if ways can be found to provide more positive science related experiences for pre-service and in-service teachers.